Apertura originaria alla tecnica dell’umano e pericolo della regressione in Bernard Stiegler - Velardi, Andrea (Mechane, 2024)
The aim of the paper is to address the issue of the ambivalence of the original opening to the technique of human being in Bernard Stiegler’s theory in order to integrate the pharmacological account of the technique as medicine and poison that characterizes the second period of his reflection to the conception deepened in the Trilogy devoted on one hand to the original intertwining among human being, technique and temporality and on the other hand to the interplay between the oblivion of Epimetheus and the hybris of Prometheus. Following Leroi-Gourhan’s paleoanthropology, that original connection involves the necessary role of technique’s externalizations that generates an amount of a deployed and relatively detached thesaurus of traces, languages and documentality called by Stiegler tertiary retention. We deepen the issue of the intertwining between externalizations and the necessity of a continuous effort of re-internalization of these ones, linked with Simondon’s psychological and social individuation, in order to avoid the degeneration of the original connection between humanity and technique in a form of regression, symbolic misery and digital nichilism.